Enzyme-inspired dry-powder polymeric catalyst for green and fast pharmaceutical manufacturing processes - Viveiros, Raquel (2022)
Principal Investigator contract IF/00915/2014 (T.C.), and a doctoral grant , a partnership from FCT/MCTES and the pharmaceutical company HOVIONE (R.V.). L.B.M. would like to acknowledge for FCT/MCTES funding with reference CEECIND/03810/2017. The NMR spectrometers in LabNMR@Cenimat are part of the National NMR Facility, supported by FCT (ROTEIRO/0031/2013 - PINFRA/22161/2016 ), co-financed by FEDER through COMPETE 2020, POCI, and PORL and FCT through PIDDAC ( POCI-01-0145-FEDER-007688 ; UID/CTM/50025/2020-2023 ). The Associate Laboratory Research Unit for Green Chemistry - Clean Technologies and Processes - LAQV is financed by national funds from FCT/MCTES ( UIDB/QUI/50006/2020 ) and cofunded by the ERDF under the PT2020 Partnership Agreement ( POCI-01-0145-FEDER-007265 ). We also acknowledge Dr. Luz Fernandes, REQUIMTE analytical services, for GC analysis. Publisher Copyright: © 2022